Ginsenoside Rg1 Ameliorates Palmitic Acid-Induced Hepatic Steatosis and Inflammation in HepG2 Cells via the AMPK/NF-κB Pathway - Xiao, Qing (Int J Endocrinol, 2019)
Nonalcoholic fatty liver disease (NAFLD) is one of the common diseases in the world, and it can progress from simple lipid accumulation to sustained inflammation. The present study was designed to investigate the effects and underlying mechanisms of ginsenoside Rg1 (G-Rg1) treatment on NAFLD in vitro. HepG2 cells were treated with palmitic acid (PA) to induce steatosis and inflammation and then successively incubated with G-Rg1. Lipids accumulation was analyzed by Oil Red O staining and intracellular triglyceride (TG) quantification. Inflammatory conditions were examined by quantifying the levels of cell supernatant alanine transaminase/aspartate aminotransferase (ALT/AST) and secretory proinflammatory cytokines, including IL-1β, IL-6, and TNF-α in the cell supernatants. Quantitative RT-PCR and western blotting were used to measure the expressions of genes and proteins associated with lipogenic synthesis and inflammation, including AMP-activated protein kinase (AMPK) and nuclear factor-kappa B (NF-κB) pathways. HepG2 cells were pretreated with an AMPK inhibitor; then, Oil Red O staining and TG quantification were performed to study the lipid deposition. Phospho-AMPK (Thr172) (p-AMPK) and phospho-acetyl-CoA carboxylase (Ser79) (p-ACCα) were quantified by immunoblotting. Immunofluorescence was performed to demonstrate the nuclear translocation of NF-κB P65. The present study showed that PA markedly increased the intracellular lipid droplets accumulation and TG levels, but decreased AMPK phosphorylation and the expressions of its downstream lipogenic genes. However, G-Rg1 alleviated hepatic steatosis and reduced the intracellular TG content; these changes were accompanied by the activation of the AMPK pathway. In addition, blocking AMPK by using the AMPK inhibitor markedly abolished the G-Rg1-mediated protection against PA-induced lipid deposition in HepG2 cells. Furthermore, G-Rg1 reduced the ALT/AST levels and proinflammatory cytokines release, which were all enhanced by PA. These effects were correlated with the inactivation of the NF-κB pathway and translocation of P65 from the cytoplasm to the nucleus. Overall, these results suggest that G-Rg1 effectively ameliorates hepatic steatosis and inflammation, which might be associated with the AMPK/NF-κB pathway.